Experimental study of emissions in single-cylinder diesel engine operating with diesel-biodiesel blends of palm oil-sunflower oil and ethanol. (August 2021) - Vergel-Ortega, M.; Valencia-Ochoa, G.; Duarte-Forero, J.
Abstract: This study investigates an alternative fuel methodology for diesel engines that focus on the influence of ethanol as an additive agent in biodiesel blends derived from the industrial liquid waste of palm oil and sunflower oil residues. Specifically, the study addresses relevant aspects of the combustion performance and emissions characteristics in a single-cylinder diesel engine. For the experimental development, four different fuels were tested: commercial diesel, a blend of biodiesel formed from the residual material of palm oil and sunflower oil (PB3SB2), two blends with an addition of 2%, and 4% ethanol in the biodiesel produced (PB3SB2E2 and PB3SB2E4). The engine operated under nine different operation modes following international testing methodologies. Results indicated that incorporating ethanol in the PB3SB2 biodiesel blend improves thermal efficiency by 0.8%. Increasing the ethanol mixing ratio to 4% provides a further efficiency improvement of up to 1.2%. The emissions analysis showed that the addition of ethanol below 4% in the biodiesel blend facilitates the minimization of pollutant levels of CO, CO2, NOx, HC, and smoke opacity compared to the biodiesel formed by the two residual oils (PB3SB2). Overall, ethanol incorporation reduced emissions levels between 7.5 and 13.87% compared to PB3SB2. In conclusion, integrating biodiesel and ethanol as additive agent emerges as a promising alternative to promote a reliable and sustainable operation in diesel engines.